Department of Pre-University Education, KarnatakaPUC Karnataka Science Class 11
Advertisement Remove all ads

X−3 (5 + 3x) - Mathematics

x−3 (5 + 3x

Advertisement Remove all ads

Solution

\[\text{ Let } u = x^{- 3} ; v = \left( 5 + 3x \right)\]
\[\text{ Then }, u = - 3 x^{- 4} ; v' = 3\]
\[\text{ Using the product rule } :\]
\[\frac{d}{dx}\left( uv \right) = uv' + vu'\]
\[\frac{d}{dx}\left[ x^3 \left( 5 + 3x \right) \right] = x^{- 3} . 3 + \left( 5 + 3x \right) \left( - 3 x^{- 4} \right)\]
\[ = 3 x^{- 3} - 15 x^{- 4} - 9 x^{- 3} \]
\[ = - 15 x^{- 4} - 6 x^{- 3}\]

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 30 Derivatives
Exercise 30.4 | Q 24 | Page 39
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×